Cycling DOF factor mediated seasonal regulation of sexual reproduction and cold response is not conserved in Physcomitrium patens - Alexander G. Freidinger; Lauren A. Woodward; Jo Trang Bùi; Gillian Doty; Shawn Ruiz; Erika Conant; Karen A. Hicks (Plant Direct)
Abstract Many land plants have evolved such that the transition from vegetative to reproductive development is synchronized with environmental cues. Examples of reproduction in response to seasonal cues can be found in both vascular and nonvascular species; however, most of our understanding of the molecular events controlling this timing has been worked out in angiosperm model systems. While the organism‐level mechanisms of sexual reproduction vary dramatically between vascular and nonvascular plants, phylogenetic and transcriptomic evidence suggest paralogs in nonvascular plants may have conserved function with their vascular counterparts. Given that Physcomitrium patens undergoes sexual reproductive development in response to photoperiodic and cold temperature cues, it is well‐suited for studying evolutionarily conserved mechanisms of seasonal control of reproduction. Thus, we used publicly available microarray data to identify genes differentially expressed in response to temperature cues. We identified two CDF‐like (CDL) genes in the P. patens genome that are the most like the angiosperm Arabidopsis thaliana CDFs based on conservation of protein motifs and diurnal expression patterns. In angiosperms, DNA‐One Finger Transcription Factors (DOFs) play an important role in regulating photoperiodic flowering, regulating physiological changes in response to seasonal temperature changes, and mediating the cold stress response. We created knockout mutations and tested their impact on sexual reproduction and response to cold stress. Unexpectedly, the timing of sexual reproduction in the ppcdl‐double mutants did not differ significantly from wild type, suggesting that the PpCDLs are not necessary for seasonal regulation of this developmental transition. We also found that there was no change in expression of downstream cold‐regulated genes in response to cold stress and no change in freezing tolerance in the knockout mutant plants. Finally, we observed no interaction between PpCDLs and the partial homologs of FKF1, an A. thaliana repressor of CDFs. This is different from what is observed in angiosperms, which suggests that the functions of CDF proteins in angiosperms are not conserved in P. patens.